Plasma dynamic synthesis of hybrid carbide-reinforced aluminium matrix composites; Particuology; Vol. 109 - Nikitin D. S. Dmitry Sergeevich; Shanenkov I. I. Ivan Igorevich; Nassyrbayev (Nasyrbaev) A. Artur; Tsimmerman (Cimmerman) A. I. Aleksandr Igorevich; Shanenkova Yu. L. Yuliya Leonidovna; Kashkarov E. B. Egor Borisovich; Li Junzhi; Han Wei (2026, 2026)
Title screen